Thousands of Novel Transcripts Identified in Mouse Cerebrum, Testis, and ES Cells Based on ribo-minus RNA Sequencing - Liu, Wanfei; Zhao, Yuhui; Cui, Peng; Lin, Qiang; Ding, Feng; Xin, Chengqi; Tan, Xinyu; Song, Shuhui; Yu, Jun; Hu, Songnian (Frontiers in Genetics, 2011)
The high-throughput next-generation sequencing technologies provide an excellent opportunity for the detection of less-abundance transcripts that may not be identifiable by previously available techniques. Here, we report a discovery of thousands of novel transcripts (mostly non-coding RNAs) that are expressed in mouse cerebrum, testis, and embryonic stem (ES) cells, through an in-depth analysis of rmRNA-seq data. These transcripts show significant associations with transcriptional start and elongation signals. At the upstream of these transcripts we observed significant enrichment of histone marks (histone H3 lysine 4 trimethylation, H3K4me3), RNAPII binding sites, and cap analysis of gene expression tags that mark transcriptional start sites. Along the length of these transcripts, we also observed enrichment of histone H3 lysine 36 trimethylation (H3K36me3). Moreover, these transcripts show strong purifying selection in their genomic loci, exonic sequences, and promoter regions, implying functional constraints on the evolution of these transcripts. These results define a collection of novel transcripts in the mouse genome and indicate their potential functions in the mouse tissues and cells.